Supplement to Draft Annual Plan 1977-78 Himachal Pradesh - Planning Commission (Planning Commission, 1977)
Due to Hon’ble Chief Minister's visit to the eastern states, the meeting of the State Planning Board Should be convened on 12th November, 1976. The draft proposals-regarding Annual Plan 1977-78 and certain change in the sectoral outlays in respect of some of the sectors. Due to shortage of time at our disposal for submission of draft Plan-to the Planning Commission, Government of India, it could be possible to incorporate the revised outlays in the Plan document only.
Himachal Pradesh Government